Overcoming physical seed dormancy in priority native species for use in arid-zone restoration programs - Erickson, T.E.; Merritt, D.J.; Turner, Shane (2016)
The relative effectiveness of wet- and dry-heat treatments on alleviating physical dormancy (PY) of seeds of seven species of Fabaceae and five species of Malvaceae was determined to optimise seed handling procedures for ecological restoration. Seeds of all species were treated at different temperatures (40-100°C) for various durations (2 and 5min of wet heat, and 5, 10 and 30min of dry heat). Prior to treatment, seeds of all species exhibited low germination (0-38%). As hypothesised, there was variation among species with respect to the efficacy of the heat treatments. In general, wet-heat treatments at temperatures >70°C for 2 or 5min were effective in breaking PY for all Fabaceae species, and two Malvaceae species, with resultant germination typically >75%. For dry-heat treatments, higher temperatures and longer durations were required to achieve similar germination results. In the three Malvaceae species that were least responsive to heat (Abutilon otocarpum, Hibiscus haynaldii and Sida echinocarpa), there was a trade-off between treatment temperature and duration; lower temperatures (<70°C) failed to alleviate PY, whereas higher temperatures either rendered seeds permeable but not germinable (70-90°C), or resulted in seeds losing viability (e.g. 100°C). Therefore, combinational dormancy (PY+physiological dormancy) appears to be present in a proportion of the seeds of these Malvaceae species (i.e. those that imbibed and remained viable, but did not germinate). Scanning electron imagery established that the majority of wet-heat treatments resulted in the rupture of the water gap in the seed testa of all species. The results clearly demonstrate that optimal heat treatments for the alleviation of PY are species-specific. Restoration practitioners handling seeds of diverse species should be mindful of treating seeds at the lowest effective temperature (70-90°C) to avoid injury through inadvertent exposure to temperatures that are higher and longer than necessary to break dormancy.